Clinical profile, outcome and clinical indicators for poor prognosis in full term babies born with severe birth asphyxia: study from tertiary care hospital from western India - Thakkar, Pareshkumar A.; Valia, Paresh; Parmar, Niyati; Javadekar, Bakul; Thakkar, Ukti P. (International Journal of Contemporary Pediatrics, 2017)
Background: The World Health Organization describes birth asphyxia as failure to initiate and sustain breathing at birth. The aim of the study was to study the clinical profile and outcome at 3 months of age of full term babies born with severe birth asphyxia and to analyze risk factors associated with adverse outcome. Methods: This was a prospective observational study carried out over period of 12 months in year 2015-16. All full-term babies born with severe birth asphyxia (n = 45) during four months period were enrolled and were followed up for 3 months. Severe birth asphyxia was defined as APGAR score 3 or less at 1 minute. Baseline characteristics, clinical profile and outcome were noted. HIE was graded as per Sarnat and Sarnat staging. Neurological Assessment at 7th day and on discharge was done and children were assessed by Amiel Tison Scale at 3 months. Multivariate analysis by linear regression was done to find risk factors associated with adverse outcome. Results: Of total 45 babies with SBA, 35 developed HIE, of which 13 (28.8%) were in HIE grade II and 13 (28.8%) were in HIE III. Mortality found was 20% while 28.5% of survivors had abnormal neurological outcome at 3 months. Multivariate analysis of risk factors shows that abnormal neurological findings on 7th day of life, APGAR ≤ 6 at 10 minute and HIE grade II or more were associated with abnormal outcome (p = 0.01). The risk factors associated with mortality were multiorgan dysfunction, difficult to control seizures, APGAR ≤4 at 10 minute (p = 0.07). Conclusions: Full term neonates with severe birth asphyxia has significant mortality and significant number of survivors has abnormal neurological outcome at 3 months of age. Presence of certain clinical indicators is associated with increased risk of adverse outcome.